2023
DOI: 10.1002/app.54253
|View full text |Cite
|
Sign up to set email alerts
|

Structure evolution and properties enhancement of polyamide‐6/polyamide‐1010 films under uniaxial and biaxial stretching

Abstract: The effect of stretching process on the structures and properties of the stretch-oriented PA6/PA1010 film was investigated during the uniaxial and biaxial stretching. The results showed that the PA6/PA1010 cast film exhibited β-form crystals, and the uniaxial stretching induced the β ! α + γ phase transition and preferential orientation along the stretching direction, while the β ! α phase transition and no preferential orientation were observed

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…In the case of the heating-treated film ( Figure 7 a), the intensity of the diffraction ring was noticeably enhanced compared with the untreated one ( Figure 5 c), indicating an increase in the crystallinity of the copolymer film. With an increase in the stretching ratio, the diffraction signals in the direction of MD became stronger than those in the TD direction accompanied by the transform into non-uniform rings with the (010) and (110) lattice planes evolving from two semicircles into two shorter arcs, suggesting an increase in the crystalline orientation of the BO-PA66/PACM6 film [ 30 , 43 ]. When the stretching ratio was further increased to 3 × 3, the intensity of the diffraction ring was further decreased.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the case of the heating-treated film ( Figure 7 a), the intensity of the diffraction ring was noticeably enhanced compared with the untreated one ( Figure 5 c), indicating an increase in the crystallinity of the copolymer film. With an increase in the stretching ratio, the diffraction signals in the direction of MD became stronger than those in the TD direction accompanied by the transform into non-uniform rings with the (010) and (110) lattice planes evolving from two semicircles into two shorter arcs, suggesting an increase in the crystalline orientation of the BO-PA66/PACM6 film [ 30 , 43 ]. When the stretching ratio was further increased to 3 × 3, the intensity of the diffraction ring was further decreased.…”
Section: Resultsmentioning
confidence: 99%
“…It can be found that the melting temperature and the crystallinity of BO-PA66/PACM6 were slightly increased with the increase in the stretching ratio (Table S4) due to the more regular arrangement of the polymer chains upon stretching. and (110) lattice planes evolving from two semicircles into two shorter arcs, suggesting an increase in the crystalline orientation of the BO-PA66/PACM6 film [30,43]. When the stretching ratio was further increased to 3 × 3, the intensity of the diffraction ring was further decreased.…”
Section: Crystallization Behavior Of Bo-pa66/pacm6 Filmsmentioning
confidence: 99%